The Effect of Job Training on Employee Performance Is Mediated by The Quality of Employees at BPJS Ketenagakerjaan Branch in Medan Raya - Sakinah Ramza; Mesra B (Yayasan Multidimensi Kreatif, 2024)
In this study, the researcher wants to see the direct and indirect influence between the training variable as an independent variable and the quality of employees as a mediation variable and employee performance as a bound variable. This type of research uses a quantitative method, this research was conducted at BPJS ketenagakerjaan Branch in Medan Raya which consists of BPJS ketenagakerjaan Medan Kota Branch Office, North Medan Branch, Tanjung Morawa Branch and Binjai Branch. The population of this study is 80 employees and the sample used is all populations using the saturated sample technique. The data source used is the primary data source and the data collection carried out is disseminated by the cluster. The research model used is phat analysis with smart PLS version 3.3.3. as a research measuring tool. The results of this study are as follows: Job training has a positive and significant effect on employee performance with the original sample value of 0.463 and P values of 0.000. Job training had a positive and significant effect on the quality of employees with the original sample value of 0.590 and p values of 0.000. Employee quality had a positive and significant effect on employee performance with an original sample value of 0.511 and p values of 0.000. Job training has a positive and significant effect on employee performance through the quality of direct employees with the original sample results of 0.302 and p values of 0.000.